The Ichneumonidae (Hymenoptera: Ichneumonoidea) of Ría Lagartos Biosphere Reserve, Yucatán, Mexico - González–Moreno, Alejandra; Bordera, Santiago (Zootaxa, 2012)
A total of 148 species and 69 genera are first records of Ichneumonidae from Ría Lagartos Biosphere Reserve (Yucatán,Mexico), raising the total number of known species and genera of the Reserve to 216 and 99 respectively. Material wascollected over a 14 months period by Malaise traps in three habitats; dry forest, savannah and coastal dune scrubland. Atotal of 4,215 individuals of Ichneumonidae are included in this paper. Of the species reported from Ría Lagartos, 89 spe-cies (49%) have a Neotropical distribution; six (3%) have been reported previously only from the Nearctic; 44 (24%) haveboth Nearctic and Neotropical distributions and 42 (24%) have been reported only from Mexico. The recorded hosts be-long to 19 families of Lepidoptera, three Coleoptera, four Hymenoptera and one Neuroptera. Most species have a higher abundance in the rainy season, and the dry forest habitat provided more species than the other habitats.